F-ATP synthase inhibitory factor 1 regulates metabolic reprogramming involving its interaction with c-Myc and PGC1α - Guo, Lishu; Gu, Zhenglong (Frontiers in Oncology, 2023)
F-ATP synthase inhibitory factor 1 (IF1) is an intrinsic inhibitor of F-ATP synthase. It is known that IF1 mediates metabolic phenotypes and cell fate, yet the molecular mechanisms through which IF1 fulfil its physiological functions are not fully understood. Ablation of IF1 favors metabolic switch to oxidative metabolism from glycolysis. c-Myc and PGC1α are critical for metabolic reprogramming. This work identified that IF1 interacted with Thr-58 phosphorylated c-Myc, which might thus mediate the activity of c-Myc and promoted glycolysis. The interaction of IF1 with PGC1α inhibited oxidative respiration. c-Myc and PGC1α were localized to mitochondria under mitochondrial stress in an IF1-dependent manner. Furthermore, IF1 was found to be required for the protective effect of hypoxia on c-Myc- and PGC1α-induced cell death. This study suggested that the interactions of IF1 with transcription factors c-Myc and PGC1α might be involved in IF1-regulatory metabolic reprogramming and cell fate.